Developing MEGA: A Geometry-Based Educational to Enhance Logical Thinking Skills And Visual-Spatial Skill - Linda Miftahurrohmah; Yes Matheos Lasarus Malaikosa; Wulan Patria Saroinsong (Universitas Islam negeri Mahmud Yunus Batusangkar, 2025)
The development of logical thinking skills and spatial visual intelligence in children aged 4ÔÇô5 years is essential for fostering early understanding of geometric concepts. Many children at this stage still experience difficulties recognizing basic geometric shapes such as squares, rectangles, triangles, and circles, along with identifying concrete examples from their surroundings. This study aims to develop and examine the MEGA (Media Edukasi Geometri Anak) application as a varied alternative learning medium to stimulate these abilities. The research applies a Research and Development (R&D) model with a one-group pretest-posttest design. A total of 25 children aged 4ÔÇô5 years from Kindergarten Muslimat Kabuh were involved, with data gathered through observational research activities. The effectiveness of the application was analyzed using the N-gain test. Results indicate that the application effectively enhances logical thinking, enabling children to better recognize and distinguish geometric shapes. Furthermore, spatial visual intelligence develops, as children become able to identify colors, name vertical and horizontal lines within geometric drawings, and relate real-world objects to their geometric forms. These findings highlight meaningful improvements in childrenÔÇÖs cognitive and spatial abilities after engaging with the MEGA application, showing its potential as an alternative learning medium in early childhood educational settings.┬á